NO VIOLENCE (CIPEEX, 2022)
THE VISION OF THE PRODUCT SHOWS THAT THE RATE OF DOMESTIC VIOLENCE HAS INCREASED IN THE LAST DECADE, ACCORDING TO STUDIES CARRIED OUT DURING A PUBLIC HEARING AT THE HUMAN RIGHTS COMMISSION, THESE CASES HAVE DOUBLED WITH THE PANDEMIC, AND ACCORDING TO DATA FROM THE SAME STUDY, IT REVEALED THAT 18% OF WOMEN WHO SUFFER FROM THE PROBLEM LIVE WITH THE AGGRESSOR, WHILE 68% OF BRAZILIAN WOMEN KNOW ONE OR MORE VICTIMS OF DOMESTIC OR FAMILY VIOLENCE. IN VIEW OF THIS PROBLEM, WE CARRIED OUT RESEARCH TOGETHER WITH THE PROFESSOR OF THE SOFTWARE REQUIREMENTS AND METRICS SUBJECT, IN ORDER TO DEVELOP A PROJECT WITH THE OBJECTIVE OF COMBATING DOMESTIC VIOLENCE, AND MINIMIZING CASES OF VIOLENCE AND FEMICIDE AS MUCH AS POSSIBLE. THE OBJECTIVE OF THIS PROJECT IS TO HELP BUILD A MORE PEACEFUL SCENARIO FOR WOMEN WHO SUFFER FROM DOMESTIC VIOLENCE, IN ORDER TO PROMOTE MORE SECURITY INSIDE THE HOMES, MORE RELIABILITY IN SECURITY SERVICES AND INTEGRITY TO THE USERS OF THE PRODUCT, IT IS WORTH REMEMBERING THAT IT IS STILL IN THE BEGINNING WITH DIFFICULT VISUALIZATIONS IN PRACTICE, BUT IT HAS THE POTENTIAL TO TRANSFORM THE WORLD WE LIVE IN TODAY FOR THE BETTER, PRESENTING NO VIOLENCE, THE PROJECT STARTED IN THE FIRST PERIOD OF SOFTWARE ENGINEERING. METHODS FOR DEVELOPMENT SUCH AS SCRUM WAS ADOPTED FOR THE DEVELOPMENT MODEL, AFTER LIFTING THE REQUIREMENTS, DEFINING THE SPRINT BACKLOG AND ESTIMATING A DEADLINE USING PERT FOR THE ESTIMATES FOR EACH REQUIREMENT SELECTED IN THE PLANNING PHASE, MAKING IT MORE CONSISTENT AND HAS INTEGRITY IN PRODUCTION, AND AS A PRODUCTION TECHNIQUE FOR THE MINIMUM VIABLE PRODUCT, WE CAN GUIDE OURSELVES USING THE POMODORO TECHNIQUE, TO FOCUS THE AMOUNT OF HOURS NEEDED ON EACH TASK TO BE DONE. WE STILL DON'T HAVE CONCRETE RESULTS OF THE PROJECT, WE ARE ONLY IN THE SECOND PERIOD OF THE COURSE, AND THE LEARNING PATH TO BE FOLLOWED IS STILL LONG TO START SEEING THE POSSIBLE RESULTS AND IMPACTS OF THIS PRODUCT, HOWEVER, WHEN WE CARRY OUT THE BANNER AND THE RESEARCH, WE WERE ABLE TO SEE THE GROWING POTENTIAL OF THIS PROJECT, USING ALL THE KNOWLEDGE SO FAR, WE WERE ABLE TO UNDERSTAND HOW THE VISION OF A PRODUCT BEGINS, AND HOW TO THINK ABOUT THE DYNAMICS AND CONSTRUCTION OF IT, GOING THROUGH DIFFERENT PHASES OF PLANNING AND DEVELOPMENT IN THEIR RESPECTIVE STAGES, HAVING COMMUNICATION WITH USERS, MODELING AND ASSEMBLING THE MINIMUM TO BE DELIVERED IN ORDER TO GRADUALLY INCREASE EACH FUNCTIONALITY AND PARTS OF THE PROJECT. IN THE VIEW OF THE GROUP AS A WHOLE, WE SAW THAT THIS PROBLEM MUST BE RESOLVED, PEOPLE HAVE THE RIGHT TO SECURITY INSIDE THEIR HOMES, WITH ALL POSSIBLE SUPPORT AND TECHNOLOGY TO ACHIEVE THE BEST POSSIBLE RESULTS.
Keywords: violência; violência doméstica; segurança